Corticosteroids in neurological disorders: The dark side. (October 2017) - Parissis, Dimitrios; Syntila, Styliani-Aggeliki; Ioannidis, Panos
Highlights: Corticosteroids may rarely induce or worsen certain neurological disorders. We give emphasis on putative pathophysiological mechanisms of this association. Neurologists should be familiar with this 'dark side' of steroids. Abstract: Corticosteroids are among the most commonly prescribed drugs by physicians of nearly all medical specialties. Their widespread use in clinical neurology is based either on randomized studies or, most often, on clinical experience and experts' opinion. Besides the well-known adverse effects of corticosteroids, they may also induce or worsen certain neurological disorders. The purpose of this review is to highlight the negative impact of these drugs on these disorders with emphasis on putative pathophysiological mechanisms of this association.